ChemInform Abstract: A ZnCl2‐Catalyzed Knoevenagel Condensation/1, 5‐Hydride Shift/Cyclization Sequence: Synthesis of Novel Spiroisoxazol‐5‐one Tetrahydroquinolines. Issue 52 (6th December 2016) - Zhao, Tuan; Zhang, Huanrui; Cui, Longchen; Wang, Changxue; Qu, Jingping; Wang, Baomin
Abstract: A concise synthesis of novel spiroisoxazolone tetrahydroquinoline derivatives is developed by an efficient ZnCl2 ‐catalyzed stereoselective Knoevenagel condensation/1, 5‐hydride shift/cyclization sequence.